2022
DOI: 10.3389/fnut.2022.889901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Frying on French Fries: The Indication Role of Physicochemical Properties on the Formation of Maillard Hazards, and the Changes of Starch Digestibility

Abstract: This study focused on the formation of Maillard hazards in air fried fries, highlighting the correlation between the resultant physical properties of the fries and the formation of Maillard hazards. In the meantime, the effects of air frying on the in vitro starch digestibility of fries were explored. Potato strips were fried at various temperatures (180–200°C) and time (12–24 min). Results indicated that the extent of browning, hardness, and the contents of Maillard hazards (acrylamide, 5-hydroxymethylfurfura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Therefore, the oil absorbency in French fries is primarily affected by the porous structures formed because of moisture evaporation and crust formation, which vary depending on the frying method employed. with previous studies [1,[36][37].…”
Section: Carbohydrate Contentsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the oil absorbency in French fries is primarily affected by the porous structures formed because of moisture evaporation and crust formation, which vary depending on the frying method employed. with previous studies [1,[36][37].…”
Section: Carbohydrate Contentsupporting
confidence: 88%
“…When amino acids and reducing sugars are heated, a chemical reaction known as the Maillard reaction takes place that produces a variety of substances. The high temperatures involved in the frying process of deep-fried foods, such as French fries, can cause the Maillard reaction to occur rapidly [1].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of AA at BD3 prepared by air fryer and deep fryer were similar (1500 μg/kg and 1600 μg/kg, respectively). In contrast, a study by Dong et al (2022) showed that air frying decreased significantly the amount of AA in French fries compared to deep frying. The slightly higher amounts of AA in deep frying could be due to the use of oil and the resulting oil oxidation, contributing to more AA formation ( Dong et al, 2022 ).…”
Section: Resultsmentioning
confidence: 81%
“…In contrast, a study by Dong et al (2022) showed that air frying decreased significantly the amount of AA in French fries compared to deep frying. The slightly higher amounts of AA in deep frying could be due to the use of oil and the resulting oil oxidation, contributing to more AA formation ( Dong et al, 2022 ). Based on our results, oven baking was the recommended cooking method for French fries.…”
Section: Resultsmentioning
confidence: 81%
“…Frying is the most common method for snack processing, resulting in characteristic colours and aromas of fried products. Furthermore, snack processed with conventional tends to have a high oil (Dong et al, 2022). Vacuum frying is a frying process that requires lower pressure, lower temperature, and less oxygen content than the conventional method.…”
Section: Introductionmentioning
confidence: 99%